Sericin based nanoformulations: a comprehensive review on molecular mechanisms of interaction with organisms to biological applications - Das, Gitishree (2021)
Background: The advances in products based on nanotechnology have directed extensive research on low-cost, biologically compatible, and easily degradable materials. Main body: Sericin (SER) is a protein mainly composed of glycine, serine, aspartic acid, and threonine amino acids removed from the silkworm cocoon (particularly Bombyx mori and other species). SER is a biocompatible material with economic viability, which can be easily functionalized due to its potential crosslink reactions. Also, SER has inherent biological properties, which makes possible its use as a component of pharmaceutical formulations with several biomedical applications, such as anti-tumor, antimicrobials, antioxidants and as scaffolds for tissue repair as well as participating in molecular mechanisms attributed to the regulation of transcription factors, reduction of inflammatory signaling molecules, stimulation of apoptosis, migration, and proliferation of mesenchymal cells. Conclusion: In this review, the recent innovations on SER-based nano-medicines (nanoparticles, micelles, films, hydrogels, and their hybrid systems) and their contributions for non-conventional therapies are discussed considering different molecular mechanisms for promoting their therapeutic applications.[Figure not available: see fulltext.]